Breastfeeding and breast cancer: a case-control study in Southern Brazil Amamentação e câncer de mama: estudo de caso-controle no Sul do Brasil - Sérgio Tessaro; Jorge U. Béria; Elaine Tomasi; Cesar G. Victora (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
To investigate the relationship between breastfeeding and breast cancer in Southern Brazil, a case-control design was employed, with two age-matched control groups. A total of 250 cases of breast cancer were identified in women from 20 to 60 years of age, with 1,020 hospital and community controls. The main study variables were occurrence of breastfeeding and duration of breastfeeding. A multivariate conditional logistic regression analysis was employed. According to the results, breastfeeding did not have a protective effect against breast cancer. The odds ratio (OR) for women who breastfed was 0.9 (95% CI: 0.8-1.2) compared to women who did not breastfeed. For women who breastfed for six months or less, the OR was 1.0 (95% CI: 0.6-1.8). In pre-menopausal women who breastfed for more than 25 months, the OR was 0.95 (95% CI: 0.5-3.5), and in post-menopausal women OR was 1.27 (95% CI: 0.5-3.1), compared to women who had not breastfeed. Para investigar esta relação, entre amamentação e câncer de mama no Sul do Brasil, utilizou-se um delineamento de caso-controle com dois grupos de controles, emparelhados por idade. Foram identificados 250 casos de câncer de mama em mulheres de 20 a 60 anos e 1.020 controles hospitalares e controles de vizinhança. As principais variáveis estudadas foram a ocorrência e o tempo da amamentação. A análise multivariada foi realizada por meio de regressão logística condicional, não encontrando efeito protetor da amamentação contra o câncer de mama. A razão de odds (RO) para quem amamentou foi de 0,9 (IC95%: 0,8-1,2) comparando-se com quem não amamentou. Para as mulheres que amamentaram por seis meses ou menos, a RO foi de 1,0 (IC95%: 0,6-1,8). Entre as mulheres na pré-menopausa que amamentaram por mais de 25 meses, a RO foi de 0,95 (IC95%: 0,5-3,5) e na pós-menopausa foi de 1,27 (IC95%: 0,5-3,1) comparando-se com o grupo das que não amamentaram.